Cytoreductive surgery with or without hyperthermic intraperitoneal chemotherapy in patients with peritoneal hepatocellular carcinoma. Issue 7 (5th August 2014) - Tabrizian, Parissa; Franssen, Bernardo; Jibara, Ghalib; Sweeney, Robert; Sarpel, Umut; Schwartz, Myron; Labow, Daniel
<x xml:space="preserve">Abstract</x> Background and Objectives The benefit of Sorafenib is not well described in patients with peritoneal hepatocellular carcinoma (HCC). Although cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) have shown favorable outcomes in certain malignancies, their role in peritoneal HCC remains unknown. We present a series of patients with peritoneal HCC treated with CRS +/− HIPEC and evaluate their clinicopathologic characteristics and outcomes. Methods Between 07/07‐08/12, 14 patients with limited disease to the peritoneum underwent CRS. Seven of these patients received additional HIPEC treatment. Primary endpoint was overall survival. Results Operative treatment was directed for metachronous peritoneal disease in the majority (92.8%) of patients. Mean intraoperative PCI was 9.9 (± 8.3) and complete mascroscopic cytoreduction (CCR 0‐1) was achieved in all but one case. Overall major morbidity rate (Clavien‐Dindo III‐IV) at 30 days was 7.1%. One postoperative death occurred in a patient with extensive tumor burden (PCI = 33, CCR2). Median follow‐up after initial surgery was 43.8 months and the median time to metachronous peritoneal recurrence was 23 months. Three‐year recurrence rate after peritoneal resection was 100%. Median survival of the cohort CCR0‐1 was 35.6 months. Conclusion Treatment of peritoneal HCC remains challenging and survival is poor. In well‐selected candidates, however, CRS +/− HIPEC may prolong survival compared to systemic therapy alone in patients with peritoneal HCC. J. Surg. Oncol. 2014 110:786–790. © 2014 Wiley Periodicals, Inc.